The challenge faced by shari'ah law in respect of distribution of inheritance in multi-ethnic communities: case study in Beaufort, Sabah, Malaysia - Nasoha, Zaini; Laluddin, Hayatullah; Mohd. Kusrin , Zuliza; Samuri , Mohd. al-Adib; Mohd. Nor, Amir Husin; Yaacob , Salmy Edawati; Muwazir, Mohd. Rzal (Medwell Journals, 2012)
The Federal Constitution has granted jurisdiction over Islamic affairs to each state through the 2nd list of the 9th schedule. Based on this jurisdiction, the states have approved laws relating to the Muslim community including distribution of deceased estate. In the context of multi-ethnic Muslim community, state customary and traditional laws pose a rather significant challenge to the effective operation of Shari'ah Courts. Result of a study conducted in 2009 indicate that element of ethnicity and custom have more or less constrained the Shari'ah Courts from carrying out this jurisdiction. It is observed that in addition to consulting the Shari'ah Court, bumiputra communities in the study areas continue to adhere to custom in matters relating to the distribution of inheritance. This study discusses this phenomena and attempt to deliberate on the approach adopted by court in handling of the relevant cases.